The Flow and Fracture of Cracked Ice: Experiments to Aid Modeling - Schulson, Erland M (1998)
I wish to establish whether the leads that form within an anisotropic ice cover at high-latitudes develop from the growth and interaction under far-field compression of pre-existing flaws, such as thermal cracks and re-frozen leads. With this in mind, my near-term objectives are to study and understand the mechanical behavior of columnar sea ice under controlled conditions and to determine the role played by pre-existing flaws. I plan to study the compressive failure pattern on scales accessible to controlled experiments, and then to compare these patterns to those seen on satellite images. See also ADM002252.